Spread Body and Exposed Body: dialogue with jean-luc nancy. Issue 3 (4th July 2021) - Falque, Emmanuel; Chabbert, Marie; Deketelaere, Nikolaas
Abstract: The question of the body spans across the work of Jean-Luc Nancy, from Noli me tangere, to Corpus and Jacques Derrida's dialogue with Nancy in On Touching . In constant conversation with Christianity ("This is my body" or Dis-Enclosure ), corporeality in Nancy can be summarised using the figure of the "exposed body ( corps ex-peausé )": a demonstration of the surface of the skin ( peau ) and an exposition of the self to the other in the sense of a "staging" ( Corpus ). In my work, the concept of the "spread body, " situated between Descartes' "extended body" and Husserl's "lived body, " is also one of a confrontation with the "This is my body" of Christianity ( The Wedding Feast of the Lamb ). In confronting one with the other, it is a matter of seeing how my expansion of the body, says something different than, or articulates differently, Jean-Luc Nancy's exposition of the body, this time drawn from the biological side though nevertheless without ceasing to be intentional. It is certainly a matter of philosophy, but also of ethics, in the possibility of describing such a body, especially in the suffering situation of palliative care ( Ethics of the Spread Body ).